Are Social Media Worth It for News Media?: Explaining News Engagement on Tumblr and Digital Traffic of News Websites. Issue 1 (3rd April 2021) - Kim, Dam Hee; Desai, Meera
ABSTRACT: News organizations, faced with financial challenges in transitioning to a digital era, have embraced social media to attract an audience. Little, however, is empirically known regarding which factors generate engagement on social media to drive traffic to dedicated news websites. To answer this question, digital traffic of top 50 news organizations and 230, 375 posts made by 41 accounts of these organizations on a social media platform, Tumblr, were analyzed. The results suggest that both still and animated images in news posts can be helpful for engagement not just linearly but in a non-linear, exponential fashion while hashtags in news posts may also positively predict digital traffic to news websites. Nonetheless, having a link to news websites in posts does not increase engagement or digital traffic to news websites. The implications of results are discussed for news organizations' digital strategies that not only engage but also inform audiences for better journalism.